Analysis of Esophageal Motility and Reflux Characteristics in Patients with Gastroesophageal Reflux Disease With or Without Extraesophageal Symptoms - Jiang, Guoping; Cong, Yanqun; Zhou, Feng; Zheng, Peifen (Turkish Journal of Gastroenterology, 2022)
Background: The pathogenesis of extraesophageal symptoms of gastroesophageal reflux disease is complex, and esophageal motilityand reflux may be involved in it. In this study, we aimed to compare esophageal motility and reflux characteristics in gastroesophageal reflux disease patients with and without extraesophageal symptoms by high-resolution manometry and multichannel intraluminalimpedance-pH monitoring.Methods: We retrospectively studied gastroesophageal reflux disease patients between January 2014 and December 2018. All patientshad undergone high-resolution manometry and multichannel intraluminal impedance-pH monitoring. The results were compared andanalyzed.Results: A total of 59 patients were included in this study. Patients were divided into 3 groups according to their main complaint: onlytypical symptoms (group A, n = 11), both typical and extraesophageal symptoms (group B, n = 33), and only extraesophageal symptoms (group C, n = 15). Compared with group A, the lower esophageal sphincter basal pressure, integrated residual pressure, and loweresophageal sphincter length were lower, and the proximal reflux percentages of a weak acid and non-acid reflux were higher in group Band group C (P < .017). The positive rate of esophageal motility disorders was lower in group A than in other groups (P < .05). The proportion of patients with multiple rapid swallows/single swallow—distal contractile integral ratio greater than 1—was higher in group A thanin other groups (P < .05).Conclusions: Decreased lower esophageal sphincter pressure and lower esophageal sphincter length, increased proximal esophagealreflux of weak acid and non-acid reflux, esophageal motility disorders, and decreased peristaltic reserve are involved in the pathogenesisof extraesophageal symptoms of gastroesophageal reflux disease